2009
DOI: 10.1002/adfm.200801064
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorescent Poly(dimethylsiloxane) for On‐Chip Temperature Measurements

Abstract: This work describes a convenient method to generate a poly(dimethylsiloxane) (PDMS) composite containing ZnO quantum dots (QDs) for whole‐chip temperature measurements. This composite is highly fluorescent and very sensitive to temperature changes (0.4 nm °C−1, compared to 0.1 nm °C−1 in commonly used CdSe QDs). It also shows extremely high fluorescent stability under various conditions over long time without phase separation or fluorescent changes. Both merits make this composite an ideal material for sensing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…PDMS/ZnO quantum dot (QD) composites have been reported by Zhou et al 78. The yellow highly fluorescent composites were prepared by the ultrasonication of ZnO QDs (0.1–1 wt%) in ethanol and PDMS prepolymer.…”
Section: Pdms Surface Modification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDMS/ZnO quantum dot (QD) composites have been reported by Zhou et al 78. The yellow highly fluorescent composites were prepared by the ultrasonication of ZnO QDs (0.1–1 wt%) in ethanol and PDMS prepolymer.…”
Section: Pdms Surface Modification Methodsmentioning
confidence: 99%
“…The inset shows the uorescence microscopy image of the channel with the dashed lines outlining the channel position. Reprinted from 78, with permission.…”
Section: Pdms Surface Modification Methodsmentioning
confidence: 99%
“…The lower transmission in the visible range may be attributed to changes in the refractive index due to the release of oleic acid, the formation of oleic acid derivatives, or the formation of a ZnO-PDMS complex. The incorporation of ZnO QDs into a bulk PDMS composite was reported earlier [34], and this system showed a difference in fluorescence response to temperature between the yellow and blue emitting dots. The authors suggested that the blue emitting dots were totally incorporated into the PDMS matrix, therefore lost their fluorescence sensitivity to temperature.…”
Section: Effect Of Cross-linkingmentioning
confidence: 91%
“…The periosteum was treated with decellularized solution (1% Triton X with 0.02% EDTA and 0.2 mg/ml DNase in phosphate‐buffered saline) for 24 hrs to remove the cells on its surface, and then was fixed on a silica wafer and lyophilized in a freeze dryer (FDU‐1100, RIKAKIKAI, Japan). After that, the as‐prepared decellularized periosteum used as an original template to fabricate the poly (dimethylsiloxane) (PDMS) negative replica 50, 51. The PDMS negative replica was produced by curing prepolymer (TSE3032, Momentive, JP) on the decellularized periosteum template.…”
Section: Methodsmentioning
confidence: 99%